Pemberitaan Media Cetak dalam Mempengaruhi Partai Politik untuk Menentukan Calon pada Pemilukada Tahun 2015 - Hairul Iman Hasibuan (UMSU, 2018)
This study aims to find out how the print media influences political parties to determine who the candidates are carried out in the Regional Head General Election in South Tapanulis Regency in 2015. The researchers examined the contents of the coverage of two local print media namely Harian Analisa and Harian Waspada. The method used is descriptive with a qualitative approach by analyzing and describing the opinions of participants, namely three political parties. The three political parties included: Golkar, PPP and Gerindra parties. Based on research, it is known and produces national printed media distributed at the district, provincial, central level and has a large reader base such as Harian Analisa and Harian Waspada to measure political parties in assessing the electability of candidates for regency in the Tapsel Regional Election on December 9 2015. In addition, the contents of the news that contains the curriculum vitae, vision and mission and the closeness of the candidates for regional heads and the community are one of the factors outside lobbying and money that can influence political parties carrying candidates in the Pemilukada Tapsel.